Aplikasi Lactobacillus plantarum NHC6 dalam Jus Nanas: Application Lactobacillus plantarum NHC6 as a Probiotic in Pineapple Juice - Ariyanto, Yogy Satria; Meryandini, Anja; Sunarti, Titi (Jurnal Sumberdaya Hayati, 2021)
Probiotics are living microorganisms if consumed in sufficient quantities can be beneficial for health. One of the potential bacteria as probiotics is Lactobacillus plantarum NHC6 is a lactic acid bacteria isolated from pineapple juice. This study aimed to test the ability of L. plantarum NHC6 as a probiotic in pineapple juice. Probiotics were stored until four weeks under 4°C and 10°C which weekly is monitored data on the amount of microbes, pH, percentage of lactic acid, and total dissolved solids in fermented pineapple juice. The result shows, the shelf time for pineapple juice under 4°C has a lower microbial reduction time rather than the juice storage under 10°C. Probiotics shelf time predicted for 4°C storage was 28.32 weeks and for 10°C storage was 8.67 weeks after production. The changes in physical properties (pH, percentage of lactic acid, and total soluble solids) in 10°C storage is much faster than that off in 4°C, this happens because there is still metabolic activity by bacteria at that temperature.